Case Series on Teicoplanin Induced Thrombocytopenia – An Issue of Concern - Zuhaib S, Mohamed Aamir (Journal of Pharmacy Practice and Community Medicine)
Teicoplanin is a glycopeptide antibiotic which inhibits peptidoglycan polymerization in gram-positive bacteria resulting in their cell death. Thrombocytopenia is a blood disorder in which platelet count falls below 100,000 cells/µl. Bleeding occurs when platelet falls below 20,000 cells/µl. In this case series, three patients with different clinical scenarios are explained who developed thrombocytopenia associated with teicoplanin administration during their course of medication. They were identified, assessed and reported for the ADR with the help of Naranjo ADR probability scale. As far as to our knowledge teicoplanin induced thrombocytopenia is not much studied and reported. In a current emerging use of higher antibiotics like teicoplanin, this is a serious life-threatening condition that has to be carefully monitored while on treatment with these types of higher antibiotics.
Keywords: Teicoplanin; Drug induced thrombocytopenia; ADR; Naranjo scale; Haemolytic anaemia